Development of the Internet-Delivered Cognitive Behaviour Therapy Undesirable Therapist Behaviours Scale (ICBT-UTBS) - Heather D. Hadjistavropoulos; Kirsten M. Gullickson; Luke H. Schneider; Blake F. Dear; Nickolai Titov (Internet Interventions, 2019)
Internet-delivered cognitive behaviour therapy (ICBT) is often provided with therapist assistance via asynchronous secure emails, but there is limited research on undesirable behaviours exhibited by therapists in their correspondence with patients. In this study, an ICBT-Undesirable Therapist Behaviour Scale (ICBT-UTBS) was developed and used to assess the nature, frequency, and correlates of undesirable therapist behaviours in routine practice. Thematic analysis was used to identify undesirable therapist behaviours in 720 emails sent to 91 randomly selected patients in the context of a previous clinical trial of transdiagnostic ICBT for depression and anxiety. The following undesirable behaviours were identified, albeit infrequently, in therapist emails: inadequate detail (6.4%), unaddressed content (4.0%), unsupportive tone (0.6%), missed correspondence (0.6%), inappropriate self-disclosure (0.6%), and unmanaged risk (0.3%). At least one undesirable behaviour was found in 10.7% of all emails coded. Moreover, 37.4% of patients received at least one email containing an undesirable therapist behaviour. Number of undesirable therapist behaviours was not correlated with patient engagement, working alliance, treatment satisfaction, or patient outcome variables. However, undesirable therapist behaviours were negatively correlated with patient gender and therapist characteristics (e.g., clinical setting, therapist profession). The results of the present study provide preliminary psychometric support for the ICBT-UTBS, a measure of ICBT treatment integrity. In the future, the ICBT-UTBS should be used in combination with the ICBT-Therapist Rating Scale (ICBT-TRS), a measure of desirable or recommended therapist behaviours, for training purposes and to monitor ICBT therapists in routine practice. Keywords: Undesirable therapist behaviours, Internet-delivered cognitive behaviour therapy, Therapist assistance, Treatment integrity, Scale development